Effect of physical exercise on the emotional and cognitive levels of patients with substance use disorder: a meta-analysis - Zheng, Yamiao; Zhao, Yiyang; Chen, Xilian; Li, Shanshan (Frontiers in Psychology, 2024)
This study investigated the impact of different modes of physical exercise on the emotional and cognitive levels of patients with Substance Use Disorder (SUD). By exploring the most effective intervention types, cycle, frequency, and duration, we aimed to provide evidence-based recommendations for the adjunctive treatment of SUD. We conducted a systematic search in five databases, including PubMed, Web of Science, The Cochrane Library, ScienceDirect, and EBSCO, from database inception up to May 2023, and identified 4,255 randomized controlled trials addressing the influence of physical exercise on the emotional and cognitive levels of SUD patients. Data extraction and analysis were performed using Review Manager 5.4 software, focusing on 11 studies that met the inclusion criteria and included 895 participants. Subsequently, a meta-analysis was conducted using Stata 16.0 software, presenting the results in the form of standardized mean differences (SMD) and 95% confidence intervals (CI). Our findings indicate that physical exercise significantly alleviates anxiety and depression in SUD patients while improving their cognitive function. Specifically, physical exercise was found to reduce anxiety (SMD=-0.726[-1.349,-0.103], P<0.05) and depression (SMD=-0.666[-1.077,-0.255], P<0.05) and enhance cognitive levels (SMD=-0.523[-0.887,-0.159], P<0.05) among patients. Subgroup analysis further revealed that SUD patients benefitted most from physical exercise when engaging in aerobic exercises lasting over 12 weeks, with a frequency exceeding 40 sessions and each session lasting more than 60 minutes. In conclusion, our study affirms that physical exercise mitigates anxiety and depression while enhancing cognitive function in SUD patients, making it an effective measure for adjunctive clinical treatment.